The Concept of Work in Yupik Eskimo Society Before and After the Russian Influx: A Linguist’s Perspective - Nikolai Vakhtin (Journal of Ethnology and Folkloristics)
The Yupik language has a word to signify ‘work’ derived from the stem qepgha(gh)- (qepghaq ‘work’ [noun], qepghaghtuq ‘he works’, qepghaghta ‘worker’, etc.) The scope of the meaning of this word changed drastically after the Russians came to Chukotka to stay in the 1930s. While in the pre-(intensive) contact times the word mainly meant ‘house work’ or ‘processing the carcass of a killed animal’, in mid-20th century it acquired new meanings, borrowing them from Russian. The usage of the word also became a replica of Russian usage: the concept acquired new dependent words, like evaluative adverbs and adjectives, or inanimate agents. This change of meaning reflected social changes that took place in the Yupik world as a result of the modernisation process of the 1950s and 1960s, and is an indicator of the deep transformation the society underwent under Russian (Soviet) influence. The paper analyses this process using two sources from two different epochs: Yupik texts recorded by Yekaterina Rubtsova in the 1940s, that is, in the pre-(intensive) contact period, and a modern Russian-Yupik dictionary compiled by Natalia Rodionova, a teacher of Yupik Eskimo at the Anadyr college, and published 70 years later, in 2014.